Issues and Challenges of Drug Addiction among Students in Malaysia - Razali, Asbah; Madon, Zainal (Advances in Social Sciences Research Journal, 2016)
The drug addiction problem is a global problem faced by all nations, and Malaysia was not exempted from this phenomenon. According to the United Nations Drug Control Programme (UNDCP), Malaysia, among Southeast Asian nations, ranks fifth in the number of drug addicts. Almost 1.2 million Malaysians are drug addicts, a considerable number considering Malaysia’s population of 28.3 million. This paper discusses issues and challenges of drug addiction among students in Malaysia. In this context, there are many factors contributing to drug abuse among students, such as individual inclination to partake in drugs, family situation and their surroundings. The role of parents, teachers, schools, and law enforcement authorities in ensuring the reduction of drug addiction is important, as drug addicts needed support from their surroundings. In fact, the success or failure of a student to quit drug use is dependent on the strong support of his environment. Previous studies and theories discusses in this paper shows that all parties play an important role in resolving this problem.